Carboxylate functionalized wool fibers for removal of Cu(II) and Pb(II) from aqueous solution. Issue 37 (8th August 2016) - Yin, Zhonglong; Chen, Min; Hu, Sheng; Cheng, Haiming
Abstract: Carboxylate groups were introduced onto wool fibers (Wool-g-COOH) by graft copolymerization with acrylic acid by initiation of potassium permanganate and oxalic acid redox system aiming at the removal of Cu(II) and Pb(II) ions from aqueous solutions. FT-IR results showed successful grafting. Batch adsorption experiments were carried out to investigate its adsorption capability to Cu(II) and Pb(II) ions. The results showed that the adsorption equilibrium could be obtained at 40 min for Cu (II) and at 60 min for Pb(II). Kinetic studies showed that the experimental data for adsorbing both Cu(II) and Pb(II) ions onto Wool-g-COOH were fitted well with pseudo-second-order kinetics. The equilibrium data could be better described by the Langmuir isotherm model than the Freundlich isotherm model for adsorbing both Cu(II) and Pb(II) ions onto Wool-g-COOH. The adsorption capacity for Cu(II) and Pb(II) ions was 66.67 and 204.1 mg/g calculated by Langmuir adsorption model, respectively. The adsorption process was favorable for adsorption of both Cu(II) and Pb(II) ions onto Wool-g-COOH. The Wool-g-COOH showed good regeneration property and reusability. The relative adsorption capacity for Cu(II) and Pb(II) ions still remained at 60.5 and 83.8%, respectively, after six times of recycling. The current study showed that Wool-g-COOH is a promising adsorbent for removing Cu(II) and Pb(II) ions from contaminated aqueous solutions.